Synonymy, Doubletness and Variability in the Ukrainian Literary Studies Terminology (Linguostylistic Studies, 2017)
The article is devoted to the problem of co-existence of the terms synonym, doublet and variant in the terminology framework of literary studies. In the domain of scientific terminology, only absolute synonyms, or doublets, may be considered as relevant, since they are the terms relating to the same denotatum (scientific concept), having the same definition, but differing: in structure (one word, composite, collocation, abbreviation), by origin (primordial word, borrowed, calqued), by the degree of novelty (archaism, neologism), sphere of use (academic science, education, professional sphere, media popularization of science), typicality of the term fixation (terminological dictionaries, sectoral encyclopedias, qualification works of research o, specialized or non-specialized collections, textbooks, manuals). Terminological variants emerge as a cosequence of completely another, purely formal process, namely phonetic or grammatical, caused by word-formation norms, accent, etc. The phenomena of terminological synonymy and variability should not be considered as negative phenomenon, since any doublet in the scientific discourse performs important functions of clarification, substitution, changes in the internal form of the term. Terminological synonymy and variability can certainly diversify and reactivate rather «dry» scientific metalanguage. Humanitarian terminology, as opposed to technical or natural sciences, cannot abandon synonymous or variant units, because they are important and vivid markers of its system organization.
Keywords: literary terminology; synonym; doublet; variant; system organization